RECONSTRUCTION OF LAND USED RIGHT EIGENDOM VALUES BASED ON JUSTICE AND LEGAL CERTAINTY - Hakim Tua Harahap; Darwinsyah Minin (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Eigendom rights is a right over the land west of Indonesia, including the rights of the fallen or been converted, by UUPA. UUPA determines that a conversion limit is per 24 September 1980. This means that the owner of the rights given 20 years to take care of the conversion. If the land is not converted, land rights eiqendom. back into the land controlled by the state. Many people tried to obtain recognition of the former land eigendom rights. Based on the formulation of the problem and research objectives, that the problem of this research included one land law policy in formulating the right to land former eigendom rights. Normative juridical approach used to determine the extent of legal principle, synchronization vertical / horizontal, and systemic law is applied, which is based on secondary data, namely primary legal materials, secondary, and tertiary. The results of the research that the conception of legal land ownership in Indonesia includes a system of feudal land law, land law west by Burgerlijk Wetboek (KUHPdt), customary land laws. Land administration system in Indonesia consists of land administration in the reign of the Netherlands, in the aftermath of independence before the entry into force of the UUPA, and according to the UUPA. Legal certainty of land rights through the conversion of the former eigendom apply for rights under the UUPA. Reconstruction of the right to land the former right eigndom based on values of justice and the rule of law, namely, Article 24 of Government Regulation No. 24 of 1997 reconstructed by adding the provisions of paragraph (3), which reads: That the provisions referred to in paragraph (2) give the right priority to the filing acquire rights on the ground as the provisions of the Basic Agrarian Law. Thereby granting the priority right to apply for rights to land former eigendom rights to public tenants or people who control the land which has been controlled by the state, and because PT. Agra Citra Kharisma has provided compensation to the rights holders of priority, then the PT. Agra Citra Kharisma acquire a priority right to apply for rights eigendom vervording No. 33. That the need of holding a confirmation of the rules governing the rights eigendom lands is to avoid confusion which would certainly harm to all parties, especially the rightsholders on the ground eigendom. Keyword : Land, Justice, Legal Certainly